Analysis of Learning Motivation in Improving Student's Cognitive Ability with Family Socio-Economic Conditions as Moderation Variables in Public High Schools, East Kampar Sub-district - Mulia, Ahmad Reski; Kartikowati, Rr. Sri; Makhdalena, Makhdalena (Journal of Educational Sciences, 2021)
Learning achievement is not influenced by socioeconomic level and environmental adaptability without being mediated by other factors. One of them is learning motivation. Considering that learning motivation can strengthen or weaken the influence of various factors that affect the learning process, this study aims to analyze the effect of learning motivation in improving students' cognitive abilities with the socio-economic conditions of the family as a moderating variable in SMA Negeri in East Kampar District. The data used consists of primary data and secondary data. The data were collected using questionnaires and documents. The study population was 567 students of SMA Negeri in East Kampar District with a sample of 235 students taken by proportional random sampling. The analytical method used moderated regression analysis. The results of the study found that the learning motivation variable had a significant effect on the cognitive abilities of SMA Negeri students in East Kampar District and the socio-economic conditions of the family had a significant effect on the cognitive abilities. The socio-economic conditions of the family can strengthen the influence of student learning motivation on the cognitive abilities.